2015
DOI: 10.1186/s12864-015-2003-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling during adventitious root formation in carnation stem cuttings

Abstract: BackgroundAdventitious root (AR) formation is a critical step in vegetative propagation of most ornamental plants, such as carnation. AR formation from stem cuttings is usually divided into several stages according to physiological and metabolic markers. Auxin is often applied exogenously to promote the development of ARs on stem cuttings of difficult-to-root genotypes.ResultsBy whole transcriptome sequencing, we identified the genes involved in AR formation in carnation cuttings and in response to exogenous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 64 publications
(73 reference statements)
5
70
0
Order By: Relevance
“…Cytokinins were shown to inhibit AR initiation but positively regulate cell division and stimulated AR elongation [34,35]. Studies in carnation indicated cuttings with higher trans-zeatin level always exhibited adventitious rooting capacity [15,16]. In this work, the content of zeatin was kept at a very low level in IBA treatment, agreeing with the previous findings that cytokinin content in basal parts of cuttings was decreased by IBA treatment [36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cytokinins were shown to inhibit AR initiation but positively regulate cell division and stimulated AR elongation [34,35]. Studies in carnation indicated cuttings with higher trans-zeatin level always exhibited adventitious rooting capacity [15,16]. In this work, the content of zeatin was kept at a very low level in IBA treatment, agreeing with the previous findings that cytokinin content in basal parts of cuttings was decreased by IBA treatment [36].…”
Section: Discussionsupporting
confidence: 89%
“…The ARs are usually generated spontaneously or in response to certain stimuli from stems, leaves, or non-pericycle tissues of older roots [13,14]. It could be divided into several stages based on their physiological and metabolic processes: a) dedifferentiation; b) cell division and c) adventitious root primordia initiation, development and outgrowth [15]. Plant hormones including auxin, abscisic acid, cytokinin and ethylene were proven to play vital roles in enhancement of AR formation, of which auxin was considered as a central player [16,17].…”
mentioning
confidence: 99%
“…By modulating gene transcription at precise times and during distinct processes, TFs are activated upon wounding, physiological illnesses and internal or external stimulation [16, 17]. To determine which TF families play vital roles in the development and maturation of watermelon fruit, the DEGs in COS and LSW177 were annotated and classified as TFs using PlantTFcat [18].…”
Section: Resultsmentioning
confidence: 99%
“…Auxin signalling starts from the FBL1‐mediated Aux/IAA degradation, prompting us to identify Aux/IAA proteins that might be targeted by PagFBL1. Aux/IAA genes exhibit differential expression under auxin treatment and are generally more responsive than ARF or TIR1/AFB genes (De Almeida et al ., ; Ivan et al ., ; Trenner et al ., ; Villacorta‐Martín et al ., ; Wen et al ., ; Xu et al ., ). We screened the candidate Aux/IAA genes that showed changes in expression during the early stages of AR formation, or else show differential expression in WT control vs OE plants undergoing AR formation.…”
Section: Resultsmentioning
confidence: 99%
“…The initiation stage of AR is characterized by cell division and organization of the root primordia (Li et al ., ). Studies in apple (De Klerk and De Jong, ; De Klerk et al ., ), chestnut (Sánchez et al ., ), Populus (Ribeiro et al ., ; Rigal et al ., ), Petunia (Ahkami et al ., ; Druege et al ., ), carnation ( Dianthus caryophyllus ) (Villacorta‐Martín et al ., ), Catalpa bungei (Wang et al ., ) and mung bean (Steffens and Rasmussen, ) reveal that the critical events that culminate in the formation of ARs in cuttings occur in the first 3–24 h, and the induction stage comprises molecular and biochemical events without visible changes. Auxin signal transduction was revealed in the transcriptome during the formation of ARs in cuttings in the first 24 h after induction of Populus (Ramírez‐Carvajal et al ., ), Petunia (Ahkami et al ., ; Druege et al ., ), mung bean ( Vigna radiata ) (Li et al ., ), carnation (Villacorta‐Martín et al ., ) and Malus xiaojinensis (Xu et al ., ).…”
Section: Discussionmentioning
confidence: 99%